2013
DOI: 10.1021/bi400382p
|View full text |Cite
|
Sign up to set email alerts
|

Heme Degradation by Staphylococcus aureus IsdG and IsdI Liberates Formaldehyde Rather Than Carbon Monoxide

Abstract: IsdG and IsdI from Staphylococcus aureus are novel heme degrading enzymes containing unusually non-planar (ruffled) heme. While canonical heme degrading enzymes, heme oxygenases, catalyze heme degradation coupled with the release of CO, in this study we demonstrate that the primary C1 product of the S. aureus enzymes is formaldehyde. This finding clearly reveals that both IsdG and IsdI degrade heme by an unusual mechanism distinct from the well-characterized heme oxygenase mechanism as recently proposed for Mh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
124
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(131 citation statements)
references
References 18 publications
6
124
0
1
Order By: Relevance
“…S7 A and B). Moreover, MS analyses of these 18 O-labeling experiments initiated from heme-MhuD are consistent with the sequential mono/dioxygenation mechanism. In the reductive O 2 activation, the mycobilin isomers appear to accommodate three oxygen atoms from O 2 , one of which is exchangeable with water ( Fig.…”
Section: Firstsupporting
confidence: 72%
See 1 more Smart Citation
“…S7 A and B). Moreover, MS analyses of these 18 O-labeling experiments initiated from heme-MhuD are consistent with the sequential mono/dioxygenation mechanism. In the reductive O 2 activation, the mycobilin isomers appear to accommodate three oxygen atoms from O 2 , one of which is exchangeable with water ( Fig.…”
Section: Firstsupporting
confidence: 72%
“…The ruffling is expected to drastically modulate the hemedependent O 2 activation to initiate this unique mechanism (14). Similar heme ruffling is observed for IsdG and IsdI (hemedegrading components of the iron regulated surface determinant system), MhuD homologs in Staphylococcus aureus, which liberate formaldehyde upon heme degradation instead of CO (17,18).…”
mentioning
confidence: 57%
“…A second class is exemplified by the IsdG family. Through a mechanism that hasn't been fully defined, this family of enzymes generates iron, the novel oxo-bilirubin chromophore staphylobilin, and formaldehyde, rather than carbon monoxide, upon the cleavage of heme (76)(77)(78). ChuS of E. coli O157:H7 may represent a third, structurally distinct class of HOs (79).…”
Section: Bacterial Iron and Heme Acquisition Systemsmentioning
confidence: 99%
“…1) (17). It was recently shown that a C1 product is indeed released by the S. aureus IsdG; however, quite unexpectedly, the major C1 product was determined to be formaldehyde (CH 2 O) instead of CO (18). Unlike CO, formaldehyde may be undetectable by animal immune systems, offering a potential selective advantage for heme-feeding pathogens that use IsdG-type enzymes (5,19,20).…”
mentioning
confidence: 99%